FUNCTIONAL RESTRICTIONS OF PERSONS WITH DISABILITIES IN THE ASPECT OF ESTIMATION OF WORK ABILITY LEVEL AND WORK SAFETY: Array - , К. В. (Municipal economy of cities. Series: «Economy science», 2018)
An important stage of the European integration movement of our country is the solution of socio-economic issues related to the support of people with persistent health problems. Regardless of the cause of disability, persons with limited abilities have the right on realization their professional and creative potential. Now in Ukraine, the situation with the allotment of work places for people with disabilities is difficult: the number of employed persons with disabilities, according to official data, does not exceed 0.5% of the total number of people with persistent health problems (in 2017 the number of employed persons with disabilities amounted to about 11.5 thousand of almost 2.4 million people). Among the main reasons that affect on the low level of employment of persons with disabilities is the imperfect mechanism of selection and adaptation of the workplace to the ability of a worker with a health problems, a biased attitude of the employer because of the necessity of additional investment in the development of the workplace and the implementation of additional occupational safety and health measures. In the absence of normative requirements in Ukraine regarding to the acceptable levels of dangerous and harmful production factors at the workplaces of persons with disabilities of different nosologies, the sections of the individual rehabilitation program, which are filled in by the Medical-Social Expert Commission, are, in fact, the only source that allows the employer to receive important information about further employment of an worker. The purpose of the article is to analyze the influence of functional restrictions on the level of human work ability in order to optimize the selection of the workplace in order to increase the efficiency and work safety. For this purpose, the article proposes an integral index of functional restriction of life activity, the growth of which clearly indicates a reduction of the level of employee work ability and the necessity to increase the attention to the organization of the workplace and technological process. The next step in the studying of the problem of employment of persons with disabilities and the solution of safety requirements is to take into account the employee's ability to fulfill certain production tasks. After all, the existing limitations of life activity of worker with disability, characterized by a combination of physical, mental and emotional abnormalities, may be partially or completely compensate by introducing adaptation mechanisms in order to provide the maximum possible level of work ability and safety under the given conditions. Keywords: employee with disabilities, employment, occupational safety, assessment.